Back and Forth in Time: Directing Age in iPSC-Derived Lineages - Cornacchia, Daniela (Brain Res, 2015)
The advent of induced pluripotent stem cells (iPSC) has transformed the classic approach of studying human disease, providing in vitro access to disease-relevant cells from patients for the study of disease pathogenesis and for drug screening. However, in spite of the broad repertoire of iPSC-based disease models developed in recent years, increasing evidence suggests that this technology might not be fully suitable for the study of conditions of old age, such as neurodegeneration. The difficulty in recapitulating late-stage features of disease in cells of pluripotent origin is believed to be a discrepancy between the fetal-like nature of iPSC-progeny and the advanced age of onset of neurodegenerative syndromes. In parallel to the issue of functional immaturity known to affect derivatives of pluripotent cells, latest findings suggest that reprogramming also subjects cells to a process of “rejuvenation”, giving rise to cells that are too “young” to manifest phenotypes of age-related diseases. Thus, following the significant progress in manipulating cellular fate, the stem cell field will now have to face the new challenge of controlling cellular age, in order to fully harness the potential of iPSC-technology to advance the research and cure of diseases of the aging brain.